Learning About Viruses: Representing Covid-19 - Manches, Andrew; Ainsworth, Shaaron (Frontiers in Education, 2022)
Covid-19 has significantly impacted children’s lives, requiring them to process multiple messages with significant emotional, social, and behavioural implications. Yet, the vast majority of these messages solely focus on behaviour. This is an oversight as children and young people can understand the biological properties and mechanisms of viruses when supported appropriately, thereby presenting an important opportunity for educators. However, like many other invisible scientific phenomena, understanding of viruses greatly depends upon how they are represented. Thus, we sought to understand the relative benefits and limitations of different forms for learning about the underlying biology of Covid-19. Applying an embodied learning lens, we analysed pictures, 3d models, gestures, dynamic visualisations, interactive representations, and extended reality identified through a state-of-the art-review. In so doing, we address the affordances and limitations of these forms in general and variation within them. We used this to develop a representational checklist that teachers and other adults can use to help them support children’s learning about the biology of Covid-19.